Anti-aging nano titanium dioxide modified nylon 6 fiber and preparation method thereof
By introducing functional molecules on the surface of nanotitanium dioxide and combining them with materials such as nitrile rubber to form modified fibers, the problem of insufficient toughness and oxidation resistance of nylon 6 fibers is solved, and better mechanical and oxidation resistance is achieved.
Patent Information
- Application Number
- CN202411783970.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Nylon 6 fiber has poor toughness and thermal oxygen aging resistance, and the poor dispersion of existing nanotitanium dioxide leads to less obvious modification effect.
By introducing hydroxyl groups to the surface of nanotitanium dioxide and combining with molecules such as functionally hindered phenols, carboxylated, terminal hydroxynitrile rubber modification, isocyanate nitrile rubber modification and tert-butylphenol nitrile rubber modification, followed by Polyamide 6 and talc powder are blended and melt-spinned to form anti-aging nanotitanium dioxide modified nylon 6 fibers.
It significantly enhances the mechanical properties and oxidation resistance of the fiber, avoids the agglomeration of nano-titanium dioxide, and uniform dispersion, improves toughness and oxidation resistance, and delays the oxidation process of the fiber.
Smart Images

Figure CN119321004A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nylon 6, in particular to an anti-aging nano titanium dioxide modified nylon 6 fiber and a preparation method thereof. Background Art
[0002] Nylon 6 is a general-purpose engineering plastic with many advantages such as good thermoplasticity, chemical resistance and solvent resistance. The fibers prepared with it as the matrix are also very popular in the field of fabrics. However, the toughness of the nylon 6 matrix itself is not strong, so the prepared fibers are also prone to stress fracture. Therefore, the traditional nylon matrix needs to be modified. As we all know, filling modification is one of the most economical and effective modification methods for organic polymer materials. Whether it is nanomaterials such as titanium dioxide with excellent filling performance or organic polymer materials such as nitrile rubber and EPDM rubber with obvious toughening effect, they can have a good modification effect on the nylon matrix. Combining nanomaterials and organic polymer materials to form a composite reinforcement material can further enhance the comprehensive properties of the nylon matrix such as mechanics and anti-oxidation.
[0003] Nano titanium dioxide is a new type of inorganic nanomaterial with unique photoelectric properties. With the development of materials science in recent years, there are more and more reports on the combination of inorganic nanomaterials and organic polymer materials to form composite materials. Chinese patents such as CN109321999A and CN104032404A disclose a feasible method for compounding nano titanium dioxide with nylon 6 to form a composite nylon 6 material with functions such as ultraviolet absorption. However, these patents often do not modify the nano titanium dioxide, and the problem of poor dispersibility of nano titanium dioxide has not been solved, resulting in an actual modification effect that is not obvious enough. Therefore, it is necessary to modify the nano titanium dioxide and further introduce functional molecules such as hindered phenols through the hydroxyl groups on its surface. While improving its dispersibility problem, it can also enrich the functionality of the nano titanium dioxide and further expand its application range.
[0004] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides an anti-aging nano-titanium dioxide modified nylon 6 fiber and a preparation method thereof, which solves the problem of poor toughness and thermal oxidation aging resistance of nylon 6 fiber.
[0005] (II) Technical solution To achieve the above object, the present invention provides the following technical solution: an anti-aging nano-titanium dioxide modified nylon 6 fiber, the preparation method of the anti-aging nano-titanium dioxide modified nylon 6 fiber comprises the following steps: (1) Add toluene solvent and nano-titanium dioxide to the reactor, and after ultrasonic dispersion, continue to add glutaric acid, mix well and transfer to an oil bath, raise the temperature to 90-110°C, stir and react at constant temperature for 2-8 hours, centrifuge after the reaction, wash and dry to obtain carboxylated titanium dioxide; (2) Adding dichloromethane solvent and carboxylated titanium dioxide into the reactor, ultrasonically dispersing for 20-40 minutes, continuing to add terminal hydroxyl nitrile rubber and catalyst, mixing evenly and transferring to an oil bath pot, reacting at 20-40° C. for 12-36 hours in a nitrogen atmosphere, centrifuging after the reaction, washing and drying to obtain terminal hydroxyl nitrile rubber modified titanium dioxide; (3) adding n-hexane solvent and hydroxy-terminated nitrile rubber modified titanium dioxide into a reactor, performing ultrasonic dispersion until completely dissolved, continuing to add hexamethylene diisocyanate, mixing evenly and transferring to an oil bath, stirring and reacting at 70-90° C. for 6-18 hours, centrifuging after the reaction, washing and drying to obtain isocyanate-based nitrile rubber modified titanium dioxide; (4) adding anhydrous toluene solvent and isocyanate-based nitrile rubber modified titanium dioxide into the reactor, performing ultrasonic dispersion, continuing to add 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and a catalyst, mixing evenly and transferring to an oil bath, raising the temperature to 60-80°C, reacting for 12-24 hours, centrifuging after the reaction, washing and drying to obtain tert-butylphenol nitrile rubber modified titanium dioxide; (5) Add polyamide 6, tert-butylphenol nitrile rubber modified titanium dioxide and 4-10% of filler talcum powder into a high-speed mixer, mix well and transfer to a melt spinning machine, set the spinning temperature to 240-260°C and the spinning rate to 12-20 cm / min, and spin to obtain anti-aging nano-titanium dioxide modified nylon 6 fiber.
[0006] Preferably, in step (1), the mass fraction of toluene is 400-1200 parts, the mass fraction of nano-titanium dioxide is 10 parts, and the mass fraction of glutaric acid is 12-30 parts.
[0007] Preferably, in step (2), the mass fraction of dichloromethane is 550-1600 parts, the mass fraction of carboxylated titanium dioxide is 10 parts, the mass fraction of terminal hydroxyl nitrile rubber is 8-25 parts, and the mass fraction of the catalyst is 2-6 parts.
[0008] Preferably, the catalyst in step (2) is dicyclohexylcarbodiimide (DCC).
[0009] Preferably, in step (3), the mass fraction of n-hexane is 200-650 parts, the mass fraction of the hydroxy-terminated nitrile rubber modified titanium dioxide is 10 parts, and the mass fraction of hexamethylene diisocyanate is 2-4 parts.
[0010] Preferably, in step (4), the mass fraction of anhydrous toluene is 350-1000 parts, the mass fraction of isocyanate-based nitrile rubber modified titanium dioxide is 10 parts, the mass fraction of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) is 1.5-3.5 parts, and the mass fraction of the catalyst is 0.02-0.04 parts.
[0011] Preferably, the catalyst in step (4) is dibutyltin dilaurate (DBTDL).
[0012] Preferably, in step (5), the mass fraction of polyamide 6 is 100 parts, and the mass fraction of tert-butylphenol nitrile rubber modified titanium dioxide is 2-6 parts.
[0013] 3. Beneficial technical effects Compared with the prior art, the present invention has the following beneficial technical effects: The anti-aging nano-titanium dioxide modified nylon 6 fiber has the advantages that under high temperature conditions, the carboxyl groups in glutaric acid can undergo esterification reaction with the hydroxyl groups on the surface of the nano-titanium dioxide to obtain carboxylated titanium dioxide; under the catalytic action of the catalyst dicyclohexylcarbodiimide, the carboxyl groups in the carboxylated titanium dioxide can undergo esterification reaction with the hydroxyl groups in the terminal hydroxyl nitrile rubber to obtain the terminal hydroxyl nitrile rubber modified titanium dioxide; the carboxyl groups in the carboxylated titanium dioxide can undergo esterification reaction with the hydroxyl groups in the terminal hydroxyl nitrile rubber to obtain the terminal hydroxyl nitrile rubber modified titanium dioxide; the isocyanate nitrile rubber modified titanium dioxide can undergo isocyanate reaction with the phenolic hydroxyl groups in 2,2'-methylenebis(4-methyl-6-tert-butylphenol) under the action of the catalyst dibutyltin dilaurate to obtain the tert-butylphenol nitrile rubber modified titanium dioxide; thus, the nitrile rubber macromolecule and the tert-butylphenol anti-aging small molecule are covalently grafted on the surface of the nano-titanium dioxide through the connection of chemical bonds, the functionality of the nano-titanium dioxide is effectively enhanced, and the application range of the nano-titanium dioxide is further expanded.
[0014] The anti-aging nano-titanium dioxide modified nylon 6 fiber is prepared by blending nylon 6, tert-butylphenol nitrile rubber modified titanium dioxide and an additive, and then melt spinning to finally prepare the anti-aging nano-titanium dioxide modified nylon 6 fiber. Since nylon 6 and nitrile rubber are both polar molecules, hydrogen bonds are easily generated between molecules, so they have good interface affinity with each other, so that the nano-titanium dioxide can be evenly dispersed in the nylon 6 matrix, and the agglomeration of the nano-titanium dioxide is avoided to a certain extent. When the nylon 6 matrix is subjected to external force, the evenly dispersed nano-titanium dioxide will form a stress concentration point, while absorbing the stress through its own high strength A large amount of stress can be absorbed by the nitrile rubber matrix at the same time. The presence of nitrile rubber can produce a large number of silver streaks around the nylon 6 matrix and absorb a large amount of stress energy. At the same time, nitrile rubber can hinder the extension of stress cracks, further enhancing the toughness of the composite fiber. The tert-butylphenol grafted on the surface of nano-titanium dioxide can absorb the free radicals generated during the oxidation of the nylon 6 matrix, consume a large number of free radicals, and prevent the chain growth that occurs during the oxidation of the nylon 6 matrix. Combined with the ultraviolet absorption performance of nano-titanium dioxide, it can effectively delay the oxidation of the composite nylon 6 fiber, thereby enhancing the comprehensive properties of the composite nylon 6 fiber, such as mechanics and anti-oxidation. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is the reaction mechanism diagram of carboxylated titanium dioxide and hydroxy-terminated nitrile rubber.
[0016] Figure 2 This is the reaction mechanism diagram of hydroxy-terminated nitrile rubber modified titanium dioxide and hexamethylene diisocyanate.
[0017] Figure 3 It is a reaction mechanism diagram of isocyanate-modified nitrile rubber with titanium dioxide and 2,2'-methylenebis(4-methyl-6-tert-butylphenol). DETAILED DESCRIPTION
[0018] To achieve the above object, the present invention provides the following embodiment: an anti-aging nano-titanium dioxide modified nylon 6 fiber, the preparation method comprising the following steps: Example 1
[0019] (1) Add 100 mL of toluene solvent and 2 g of nano-titanium dioxide into the reactor, and after ultrasonic dispersion, continue to add 2.4 g of glutaric acid, mix well, and transfer to an oil bath pot, raise the temperature to 90 ° C, and stir at constant temperature for 2 h. After the reaction is completed, centrifuge, wash and dry to obtain carboxylated titanium dioxide; (2) Add 90 mL of dichloromethane solvent and 2 g of carboxylated titanium dioxide into the reactor, perform ultrasonic dispersion for 20 min, continue to add 1.6 g of terminal hydroxyl nitrile rubber and 0.4 g of dicyclohexylcarbodiimide, mix well and transfer to an oil bath, react at 20 °C for 12 h in a nitrogen atmosphere, centrifuge after the reaction, wash and dry to obtain terminal hydroxyl nitrile rubber modified titanium dioxide; (3) Add 65 mL of n-hexane solvent and 2 g of terminal hydroxyl nitrile rubber modified titanium dioxide into the reactor, disperse by ultrasonic until completely dissolved, continue to add 0.4 g of hexamethylene diisocyanate, mix well and transfer to an oil bath, stir and react at 70 ° C for 6 h, centrifuge after the reaction, wash and dry to obtain isocyanate-based nitrile rubber modified titanium dioxide; (4) Add 85 mL of anhydrous toluene solvent and 2 g of isocyanate-based nitrile rubber modified titanium dioxide into the reactor, disperse by ultrasonication, continue to add 0.5 g of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and 0.004 g of dibutyltin dilaurate, mix well and transfer to an oil bath, raise the temperature to 60°C, react for 12 h, centrifuge after the reaction, wash and dry to obtain tert-butylphenol nitrile rubber modified titanium dioxide; (5) Add 50 g of polyamide 6, 1 g of tert-butylphenol nitrile rubber modified titanium dioxide and 2% of filler talcum powder into a high-speed mixer, mix well and transfer to a melt spinning machine, set the spinning temperature to 240 °C and the spinning rate to 12 cm / min, and spin to obtain anti-aging nano-titanium dioxide modified nylon 6 fiber.
[0020] Example 2
[0021] (1) Add 140 mL of toluene solvent and 2 g of nano-titanium dioxide into the reactor, and after ultrasonic dispersion, continue to add 3.3 g of glutaric acid, mix well, and transfer to an oil bath pot, raise the temperature to 95 ° C, and stir at constant temperature for 3 hours. After the reaction is completed, centrifuge, wash and dry to obtain carboxylated titanium dioxide; (2) Add 150 mL of dichloromethane solvent and 2 g of carboxylated titanium dioxide to the reactor, perform ultrasonic dispersion for 25 min, continue to add 2.4 g of terminal hydroxyl nitrile rubber and 0.6 g of dicyclohexylcarbodiimide, mix well and transfer to an oil bath, react at 25 °C for 16 h in a nitrogen atmosphere, centrifuge after the reaction, wash and dry to obtain terminal hydroxyl nitrile rubber modified titanium dioxide; (3) Add 80 mL of n-hexane solvent and 2 g of terminal hydroxyl nitrile rubber modified titanium dioxide into the reactor, disperse by ultrasonic until completely dissolved, continue to add 0.5 g of hexamethylene diisocyanate, mix well and transfer to an oil bath, stir and react at 75 °C for 8 h, centrifuge after the reaction, wash and dry to obtain isocyanate-based nitrile rubber modified titanium dioxide; (4) Add 120 mL of anhydrous toluene solvent and 2 g of isocyanate-based nitrile rubber modified titanium dioxide into the reactor, disperse by ultrasonication, continue to add 0.55 g of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and 0.005 g of dibutyltin dilaurate, mix well and transfer to an oil bath, raise the temperature to 65°C, react for 15 h, centrifuge after the reaction, wash and dry to obtain tert-butylphenol nitrile rubber modified titanium dioxide; (5) Add 50 g of polyamide 6, 1.5 g of tert-butylphenol nitrile rubber modified titanium dioxide and 3% of filler talcum powder into a high-speed mixer, mix well and transfer to a melt spinning machine, set the spinning temperature to 245 ° C and the spinning rate to 14 cm / min, and spin to obtain anti-aging nano-titanium dioxide modified nylon 6 fiber.
[0022] Example 3
[0023] (1) Add 200 mL of toluene solvent and 2 g of nano-titanium dioxide into the reactor, and after ultrasonic dispersion, continue to add 4.2 g of glutaric acid, mix well, and transfer to an oil bath pot, raise the temperature to 100 ° C, and stir at constant temperature for 4 hours. After the reaction is completed, centrifuge, wash and dry to obtain carboxylated titanium dioxide; (2) Add 180 mL of dichloromethane solvent and 2 g of carboxylated titanium dioxide into the reactor, perform ultrasonic dispersion for 30 min, continue to add 3.2 g of terminal hydroxyl nitrile rubber and 0.8 g of dicyclohexylcarbodiimide, mix well and transfer to an oil bath, react at 30 ° C for 24 h in a nitrogen atmosphere, centrifuge after the reaction, wash and dry to obtain terminal hydroxyl nitrile rubber modified titanium dioxide; (3) Add 120 mL of n-hexane solvent and 2 g of terminal hydroxyl nitrile rubber modified titanium dioxide into the reactor, disperse by ultrasonic until completely dissolved, continue to add 0.6 g of hexamethylene diisocyanate, mix well and transfer to an oil bath, stir and react at 80 ° C for 12 h, centrifuge after the reaction, wash and dry to obtain isocyanate-based nitrile rubber modified titanium dioxide; (4) Add 180 mL of anhydrous toluene solvent and 2 g of isocyanate-based nitrile rubber modified titanium dioxide into the reactor, disperse by ultrasonication, continue to add 0.6 g of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and 0.006 g of dibutyltin dilaurate, mix well and transfer to an oil bath, raise the temperature to 70°C, react for 18 h, centrifuge after the reaction, wash and dry to obtain tert-butylphenol nitrile rubber modified titanium dioxide; (5) Add 50 g of polyamide 6, 2 g of tert-butylphenol nitrile rubber modified titanium dioxide and 4% of filler talcum powder into a high-speed mixer, mix well and transfer to a melt spinning machine, set the spinning temperature to 250 °C and the spinning rate to 16 cm / min, and spin to obtain anti-aging nano-titanium dioxide modified nylon 6 fiber.
[0024] Example 4
[0025] (1) Add 240 mL of toluene solvent and 2 g of nano-titanium dioxide into the reactor, and after ultrasonic dispersion, continue to add 5.1 g of glutaric acid, mix well, and transfer to an oil bath pot, raise the temperature to 105 ° C, and stir at constant temperature for 6 hours. After the reaction is completed, centrifuge, wash and dry to obtain carboxylated titanium dioxide; (2) Add 200 mL of dichloromethane solvent and 2 g of carboxylated titanium dioxide into the reactor, perform ultrasonic dispersion for 35 min, continue to add 4 g of terminal hydroxyl nitrile rubber and 1 g of dicyclohexylcarbodiimide, mix well and transfer to an oil bath, react at 35 °C for 32 h in a nitrogen atmosphere, centrifuge after the reaction, wash and dry to obtain terminal hydroxyl nitrile rubber modified titanium dioxide; (3) Add 180 mL of n-hexane solvent and 2 g of terminal hydroxyl nitrile rubber modified titanium dioxide into the reactor, disperse by ultrasonic until completely dissolved, continue to add 0.7 g of hexamethylene diisocyanate, mix well and transfer to an oil bath, stir and react at 85 °C for 16 h, centrifuge after the reaction, wash and dry to obtain isocyanate-based nitrile rubber modified titanium dioxide; (4) Add 200 mL of anhydrous toluene solvent and 2 g of isocyanate-based nitrile rubber modified titanium dioxide into the reactor, perform ultrasonic dispersion, continue to add 0.65 g of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and 0.007 g of dibutyltin dilaurate, mix well and transfer to an oil bath, raise the temperature to 75°C, react for 20 h, centrifuge after the reaction, wash and dry to obtain tert-butylphenol nitrile rubber modified titanium dioxide; (5) Add 50 g of polyamide 6, 2.5 g of tert-butylphenol nitrile rubber modified titanium dioxide and 4% of filler talcum powder into a high-speed mixer, mix well and transfer to a melt spinning machine, set the spinning temperature to 255 ° C and the spinning rate to 18 cm / min, and spin to obtain anti-aging nano-titanium dioxide modified nylon 6 fiber.
[0026] Example 5
[0027] (1) Add 270 mL of toluene solvent and 2 g of nano-titanium dioxide into the reactor, and after ultrasonic dispersion, continue to add 6 g of glutaric acid, mix well, and transfer to an oil bath pot, raise the temperature to 110 ° C, and stir at constant temperature for 8 hours. After the reaction is completed, centrifuge, wash and dry to obtain carboxylated titanium dioxide; (2) Add 240 mL of dichloromethane solvent and 2 g of carboxylated titanium dioxide into the reactor, perform ultrasonic dispersion for 40 min, continue to add 5 g of terminal hydroxyl nitrile rubber and 1.2 g of dicyclohexylcarbodiimide, mix well and transfer to an oil bath, react at 40 ° C for 36 h in a nitrogen atmosphere, centrifuge after the reaction, wash and dry to obtain terminal hydroxyl nitrile rubber modified titanium dioxide; (3) Add 195 mL of n-hexane solvent and 2 g of terminal hydroxyl nitrile rubber modified titanium dioxide into the reactor, disperse by ultrasonic until completely dissolved, continue to add 0.8 g of hexamethylene diisocyanate, mix well and transfer to an oil bath, stir and react at 90 ° C for 18 h, centrifuge after the reaction, wash and dry to obtain isocyanate-based nitrile rubber modified titanium dioxide; (4) Add 230 mL of anhydrous toluene solvent and 2 g of isocyanate-based nitrile rubber modified titanium dioxide into the reactor, disperse by ultrasonication, continue to add 0.7 g of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and 0.008 g of dibutyltin dilaurate, mix well and transfer to an oil bath, raise the temperature to 80°C, react for 24 h, centrifuge after the reaction, wash and dry to obtain tert-butylphenol nitrile rubber modified titanium dioxide; (5) Add 50 g of polyamide 6, 3 g of tert-butylphenol nitrile rubber modified titanium dioxide and 5% of filler talcum powder into a high-speed mixer, mix well and transfer to a melt spinning machine, set the spinning temperature to 260 ° C and the spinning rate to 20 cm / min, and spin to obtain anti-aging nano-titanium dioxide modified nylon 6 fiber.
[0028] Comparative Example 1 (1) Add 120 mL of toluene solvent and 2 g of nano-titanium dioxide into the reactor, and after ultrasonic dispersion, continue to add 2.8 g of glutaric acid, mix well, and transfer to an oil bath pot, raise the temperature to 95 ° C, and stir at constant temperature for 3 hours. After the reaction is completed, centrifuge, wash and dry to obtain carboxylated titanium dioxide; (2) Add 120 mL of dichloromethane solvent and 2 g of carboxylated titanium dioxide to the reactor, perform ultrasonic dispersion for 25 min, continue to add 1.8 g of terminal hydroxyl nitrile rubber and 0.5 g of dicyclohexylcarbodiimide, mix well and transfer to an oil bath, react at 25 °C for 14 h in a nitrogen atmosphere, centrifuge after the reaction, wash and dry to obtain terminal hydroxyl nitrile rubber modified titanium dioxide; (3) Add 50 g of polyamide 6, 1.2 g of terminal hydroxyl nitrile rubber modified titanium dioxide and 2.5% of filler talcum powder into a high-speed mixer, mix well and transfer to a melt spinning machine, set the spinning temperature to 245 ° C and the spinning rate to 13 cm / min, and spin to obtain nano-titanium dioxide modified nylon 6 fiber.
[0029] The composite fibers in the examples and comparative examples were prepared into fiber membranes with a specification of 5 cm×5 cm, and the tensile strength, elongation at break, and tensile strength and elongation at break after thermal oxidation in an oven at 240° C. for 360 h were tested using a WH-70 tensile tester.
[0030]
Claims
1. An anti-aging nano-titanium dioxide modified nylon 6 fiber, characterized in that: The following steps are involved: (1) Add nano-titanium dioxide to toluene solvent, disperse it evenly by ultrasonication, then continue to add glutaric acid, mix evenly and transfer to an oil bath, raise the temperature to 90-110°C, stir and react at constant temperature for 2-8h, centrifuge after the reaction, wash and dry to obtain carboxylated titanium dioxide; (2) Add carboxylated titanium dioxide to dichloromethane solvent, perform ultrasonic dispersion for 20-40 minutes, continue to add hydroxy-terminated nitrile rubber and catalyst, mix well and transfer to an oil bath, react at 20-40° C. for 12-36 hours in a nitrogen atmosphere, centrifuge after the reaction, wash and dry to obtain hydroxy-terminated nitrile rubber modified titanium dioxide; (3) Adding the hydroxy-terminated nitrile rubber modified titanium dioxide to n-hexane solvent, ultrasonically dispersing until completely dissolved, continuing to add hexamethylene diisocyanate, mixing evenly and transferring to an oil bath, stirring and reacting at 70-90° C. for 6-18 hours, centrifuging after the reaction, washing and drying to obtain isocyanate-based nitrile rubber modified titanium dioxide; (4) adding isocyanate-based nitrile rubber modified titanium dioxide to anhydrous toluene solvent, ultrasonically dispersing, and continuing to add 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and a catalyst, mixing evenly and transferring to an oil bath, raising the temperature to 60-80°C, reacting for 12-24 hours, centrifuging after the reaction, washing and drying to obtain tert-butylphenol nitrile rubber modified titanium dioxide; (5) Add polyamide 6, tert-butylphenol nitrile rubber modified titanium dioxide and 4-10% of filler talcum powder into a high-speed mixer, mix well and transfer to a melt spinning machine, set the spinning temperature to 240-260°C and the spinning rate to 12-20 cm / min, and spin to obtain anti-aging nano-titanium dioxide modified nylon 6 fiber.
2. The anti-aging nano-titanium dioxide modified nylon 6 fiber according to claim 1, characterized in that: In the step (1), the mass fraction of toluene is 400-1200 parts, the mass fraction of nano-titanium dioxide is 10 parts, and the mass fraction of glutaric acid is 12-30 parts.
3. The anti-aging nano-titanium dioxide modified nylon 6 fiber according to claim 1, characterized in that: In the step (2), the mass fraction of dichloromethane is 550-1600 parts, the mass fraction of carboxylated titanium dioxide is 10 parts, the mass fraction of terminal hydroxyl nitrile rubber is 8-25 parts, and the mass fraction of the catalyst is 2-6 parts.
4. The anti-aging nano-titanium dioxide modified nylon 6 fiber according to claim 1, characterized in that: The catalyst in step (2) is dicyclohexylcarbodiimide.
5. The anti-aging nano-titanium dioxide modified nylon 6 fiber according to claim 1, characterized in that: In the step (3), the mass fraction of n-hexane is 200-650 parts, the mass fraction of the terminal hydroxyl nitrile rubber modified titanium dioxide is 10 parts, and the mass fraction of hexamethylene diisocyanate is 2-4 parts.
6. The anti-aging nano-titanium dioxide modified nylon 6 fiber according to claim 1, characterized in that: In the step (4), the mass fraction of anhydrous toluene is 350-1000 parts, the mass fraction of isocyanate-based nitrile rubber modified titanium dioxide is 10 parts, the mass fraction of 2,2'-methylenebis(4-methyl-6-tert-butylphenol) is 1.5-3.5 parts, and the mass fraction of the catalyst is 0.02-0.04 parts.
7. The anti-aging nano-titanium dioxide modified nylon 6 fiber according to claim 1, characterized in that: The catalyst in step (4) is dibutyltin dilaurate.
8. The anti-aging nano-titanium dioxide modified nylon 6 fiber according to claim 1, characterized in that: In the step (5), the mass fraction of polyamide 6 is 100 parts, and the mass fraction of tert-butylphenol nitrile rubber modified titanium dioxide is 2-6 parts.
Citation Information
Patent Citations
Preparation method of semi-dull nylon 6 filament
CN104032404A
High-effective far-infrared and anti-ultraviolet nylon 6 fiber and preparation method thereof
CN109321999A
Cited By
Preparation method of reactive antioxidant grafted modified nylon 6 and film thereof
CN120965948A